2020
DOI: 10.21203/rs.3.rs-119008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Revealed Candidate Genes Potentially Related to Desiccation Sensitivity of Recalcitrant Quercus variabilis Seeds

Abstract: Background: Chinese cork oak (Quercus variabilis) is a widely distributed and highly valuable deciduous broadleaf tree from both ecological and economic perspectives. Seeds of Q. variabilis are recalcitrant, i.e., sensitive to desiccation, which affects their storage and long-term preservation of germplasm. However, little is known about the underlying mechanism of desiccation sensitivity of Q. variabilis seeds. Results: In this study, the seeds were desiccated with silica gel for 0 day (control, CK), one day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Kristina and Sharon [28] found that the sucrose content of cotyledons of Quercus alba was increased in the later stages of drying. The soluble sugar content was increased in recalcitrant seeds of Quercus variabilis [29] during drying.…”
Section: Introductionmentioning
confidence: 99%
“…Kristina and Sharon [28] found that the sucrose content of cotyledons of Quercus alba was increased in the later stages of drying. The soluble sugar content was increased in recalcitrant seeds of Quercus variabilis [29] during drying.…”
Section: Introductionmentioning
confidence: 99%